1997
DOI: 10.1016/s0005-2736(97)00132-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of annexin V-dependent Ca2+ movement in large unilamellar vesicles by K201, a new 1,4-benzothiazepine derivative

Abstract: Examination was made of the effect of annexin V on Ca2+ movement into large unilamellar vesicles (LUV) using fura-2, a calcium-sensitive fluorescent dye. To avoid the possible difficulties relating to the addition of annexin V and/or Ca2+ in fura-2-loaded LUV, the burst method was used. LUV, preincubated with rat annexin V in the presence of Ca2+, were collected by centrifugation and resuspended, and then burst with Triton X-100 in the presence of fura-2. Inward Ca2+ movement across the artificial lipid membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 25 publications
1
29
0
1
Order By: Relevance
“…The 1,4-benzothiazepine derivative K-201, a specific annexin Ca 2ϩ channel blocker (19,20,31), inhibited Ca 2ϩ influx into liposomes mediated by annexin II, V, or VI in a dose-dependent manner (Fig. 2).…”
Section: Resultsmentioning
confidence: 94%
“…The 1,4-benzothiazepine derivative K-201, a specific annexin Ca 2ϩ channel blocker (19,20,31), inhibited Ca 2ϩ influx into liposomes mediated by annexin II, V, or VI in a dose-dependent manner (Fig. 2).…”
Section: Resultsmentioning
confidence: 94%
“…The drug inhibited the myo®brillar overcontraction induced by high extracellular Ca 2+ combined with epinephrine and/ or ca eine (Kaneko, 1994). Kaneko et al (1997) ascribed the cardioprotective e ect to the inhibitory e ect on annexin V. More recently Inagaki, et al (2000) have demonstrated that JTV-519 activates speci®cally d-isoform of protein kinese C through a receptor-independent mechanism and thereby induces pharmacological preconditioning. They concluded that the cardioprotective e ect of JTV-519 cannot be attributed to the Ca 2+ channel blocking action although the drug inhibited the L-type Ca 2+ current (I Ca ) in concentrations higher than 1 mM (Kimura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…JTV-519 (K201), a 1,4-benzothiazepine, was noted to have effects on intracellular Ca 2+ (35) and cardioprotective effects (36). However, the target was not known and there was no mechanism of action for JTV-519.…”
Section: Fixing Leaky Ryr2 Channelsmentioning
confidence: 99%